The Quality Characteristics of Distal Radius Fractures in Patients Admitted to Emergency Department Dr. Moh. Hoesin Hospital Palembang during January-December 2020 - Obed Yosia; Nur Rachmat Lubis (Jurnal RSMH Palembang, 2021)
Fracture cases increases in globalization era. The 8-15% reported cases were distal radius fracture (DRF). The epidemiology data is the foundation of diagnostic and management for DRF patients. However, this has not been studied in Indonesian patients. As a result, the authors decided to study the picture of DRF patients in the Indonesian subpopulation, especially in the Central General Hospital Dr. Mohammad Hoesin (RSMH) Palembang. This research is a descriptive observational study at RSMH Palembang in January-December 2020 with variables of age, sex, mechanism of injury, types of fractures, radial inclination and volar tilt as the parameter of DRF severity. All of these variables are components of the assessment on the medical record. The data in this study were 29 cases and described with the age, sex, mechanism of injury, types of fractures, radial inclination and volar tilt. The most common DRF occurred at the youth age between less 13-25 years (41.4%). DRF happened more in male (75,9%) patients than the female (24.1%) ones. The most common type of fracture is Colles (44.8%). Motorcycle crash (58.6%) is the most common mechanism of injury in DRF. The abnormal radial inclination occurred in 82% cases. Severe volar tilt counted 85% of DRF in this study. DRF happened mostly in youth, male, and motorcycle crash. Colles fracture is the most commonly type of DRF case.